Enhancing Non-English University Students’ Speaking Ability through Debate Technique - Siti Masluha; Utami Swari (Merwinspy Publisher, 2023)
In the English language, speaking is the ultimate goal. Its foundation is communication, which develops into a learning function. This study uses the debate strategy to enhance students' communication abilities. The purpose of this study is to determine whether using debate strategies in speaking classes can help students become proficient speakers and to examine the classroom dynamics involved in doing so. This study employed collaborative classroom action research, which was written for two cycles before being put into practice and reviewed to classify all the information, including the action's success or failure. There were two cycles associated with the use of debate techniques in teaching speaking at the Management Study Program: cycle one and cycle two. Thirty students from A class are the participants in this investigation.